Midgut immune profiling and functional characterization of Aedes aegypti ABC transporter gene(s) using systemic and local bacterial challenges - Vikas Kumar; Shilpi Garg; Diksha Sisodia; Lalita Gupta; Sanjeev Kumar; Vishal Saxena (Parasites & Vectors)
Abstract Background The mosquito midgut is crucial for digestion and immune interactions. It produces several immune factors that protect the organ from invading pathogens and can limit their propagation. Studies on mosquito midgut transcriptome following pathogen exposure have revealed the presence of non-canonical immune genes, such as ABC transporters, whose function in insect immunity remains unexplored. Therefore, this study focuses on identifying and characterising the immune role of ABC transporters in the midgut of Aedes aegypti, a primary arboviral vector. Methods To identify the midgut-expressed ABC transporters, the mosquitoes were challenged with a mixture of gram-negative (Escherichia coli) and gram-positive (Micrococcus luteus) bacteria, and the expression of all ABC transporters was analysed with PCR using gene-specific primers. Furthermore, the transcriptional alterations of midgut ABC transporters were explored at different time points upon a thoracic nano-injection (systemic challenge) or infectious blood meal (local challenge) of the bacterial mixture through quantitative real-time PCR (qPCR), and one gene was selected for RNAi-mediated gene silencing and its role assessment in midgut immune responses. Results The expression of all 48 microbial-induced midgut-expressing Ae. aegypti ABC transporter genes upon systemic or local bacterial challenges was analyzed. Based on the transcriptomic data and potential immune expression similar to the well-known immune gene defensin, AaeABCG3 was selected for RNAi-mediated gene silencing and characterization. The AaeABCG3 gene silencing exhibited a significant reduction of midgut bacterial load through the induction of nitric oxide synthase (NOS) in sugar-fed and systemic bacterial-challenged mosquitoes. In contrast, midgut bacterial load was significantly regulated by induction of defensin A and cecropin G in the late hours of local bacterial challenges in AaeABCG3-silenced mosquitoes. Conclusions The silencing of AaeABCG3 modulated the mosquito midgut immune response and disturbed the midgut microbiota homeostasis. The systemic immune responses of AaeABCG3-silenced mosquitoes were influenced by the JAK-STAT pathway with no induction of Toll and IMD immune pathways. Interestingly, Toll and IMD immune pathways actively participated in the late hours of local bacterial challenges, suggesting that the route of infection influences these immune responses; however, the molecular mechanism behind these phenomena still needs to be explored. Overall, this work provides significant insight into the importance of ABC transporters in mosquito immunity. Graphical Abstract